COVID-19 and Mucormycosis Coinfection: How Challenging It Is. (7th April 2022) - Nayak, Niranjan; Khan, Erum; Panigrahi, Debadatta
Abstract : Recently, cases of rhinoorbital mucormycosis in people diagnosed with COVID-19 have been reported from India particularly. Diabetes mellitus though happens to be an independent risk factor both for severe COVID-19 and mucormycosis, administration of steroids is attributed as a precipitating factor for acquiring the comorbid condition. This opportunistic fungal infection is highly angioinvasive in nature because of which, clinical outcome of infection is invariably poor, especially with rhinocerebral or rhinoorbitocerebral variety of mucormycosis. However, effective management depends upon timely and accurate diagnosis and parenteral administration of amphotericin B. At the same time, judicious use of steroids is a key factor. In addition, glycemic control in those who are severely diabetic is strongly advocated. Exenteration of an eyeball may be indicated if cavernous sinus and intracranial spread are anticipated. Therefore, in order to facilitate faster healing and better penetration of antifungal drugs, surgical debridement of the paranasal sinus cavities and removal of dead tissue from the sinuses are recommended.